Long-Run Productivity Shifts and Cyclical Fluctuations : Evidence for Italy - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2005)
Using unobserved stochastic components and Kalman filter techniques, the paper assesses the relative importance of transitory and permanent shifts in Italian real GDP within a production function framework. Evidence suggests that the increase in hours worked that has accompanied pension and labor market reforms accounts for the bulk of low-frequency variation in growth, but points to factor utilization as the main driver of business cycle fluctuations. In contrast with the predictions of standard Real Business Cycle models, a positive shock to the underlying rate of total factor productivity growth generates a slight decline in hours, whereas the response of output to the same shock is found to be positive.